EVALUASI PROGRAM PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT (PAMSIMAS) DI DESA PASIR BATU MANDI KECAMATAN SUNGAI LALA KABUPATEN INDRAGIRI HULU TAHUN 2018 - Ratih Sanima; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Community-Based Water Supply and Sanitation Program (PAMSIMAS) is one of the government's strategic programs in the context of realizing clean and healthy living communities through the provision of community-based water supply and sanitation services. Indragiri Hulu District has been implementing the PAMSIMAS program since 2008. The number of villages that received the PAMSIMAS program is spread out in each sub-district. The majority of non-functioning villages is in Sungai Lala and Pasir Batu Mandi sub-district is the village that receives the lowest percentage of proper sanitation compared to other villages since more than half of the villagers does not have access to proper sanitation. This research aims to know the evaluation of the PAMSIMAS program and the factors that hampers the evaluation of the PAMSIMAS program in Pasir Batu Mandi Village in 2018. The location of the research is in Pasir Batu Mandi Village, Sungai Lala sub-district, Indragiri Hulu District. Furthermore, data collection technique is carried out by using interview and documentation. The results of the research indicate that the evaluation of PAMSIMAS program in Pasir Batu Mandi Village in 2018 uses six indicators of evaluation criteria, namely effectiveness, efficiency, adequacy, leveling, responsiveness, and accuracy. From all these aspects, it can be seen that the construction of the PAMSIMAS program is done well physically but the research shows that various achievements before and after the program have not changed for a better provision of clean water and sanitation to the community. PAMSIMAS is not used by the community since the village is along the riverbank. The budget of the PAMSIMAS program runs smoothly but the results given at the PAMSIMAS sustainability stage are in a non-functioning condition (red) and the inhibiting factors affecting the PAMSIMAS program include external factors namely unchanging of people's lifestyle, lack of community participation in the PAMSIMAS program, unfunctional facilities and drought springs. While internal factors, namely lack of coordination and less active BPSPAMS.Keywords: Pamsimas, Effectiveness, Efficiency, Adequacy, Leveling, Responsiveness, Accuracy